Analysis of the Concept of Justice in Pricing from the Perspective of Islamic Business Ethics - Zainol Fata; Ilyas Nurul Azam (Sekolah Tinggi Agama Islam At-Tahdzib Ngoro Jombang, 2025)
This study examines the concept of justice in pricing from the perspective of Islamic business ethics. Islam emphasizes that price is not merely a transactional number, but a moral instrument reflecting justice, balance, and public benefit (maslahah) for all parties. Fair pricing should be based on principles of justice, honesty, transparency, and the rejection of harmful practices such as gharar, riba, and ihtikār. The research employed a library research method with a descriptive-analytical approach, reviewing classical and contemporary literature related to Islamic economics and business ethics. The results indicate that fair pricing reflects the proportional value of goods or services, protects consumer rights, ensures reasonable profits for producers, and creates blessings in transactions. The application of these principles is increasingly relevant in the context of globalization and modern business practices, including intense competition, changing consumer behavior, and market digitalization. Therefore, pricing according to Islamic business ethics not only supports business sustainability but also ensures broad societal welfare